How Corporate Governance Practices Affect the Cost of Debt: A Cross-Country Comparison of Pakistan and India - Nazir, Muhammad Umair (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 2 (2021)DO - 10.24843/JIAB.2021.v16.i02.p01, 2021)
This study aims to empirically investigate the association between the corporate governance practices and cost of debt between Pakistan and India. Pakistani and Indian listed firms and it is necessary by law to publish their annual reports with the recommended corporate Governance Codes. Corporate Governance practices had a powerful momentum in the crises of 1929-1933 in USA. In this study we used data from 2014-2017 with published compliance from 100 non-financial companies of Pakistan and India. This study discloses that better level of corporate governance is an essential tool for decreasing the cost of debt. This research gives an addition in empirical by adding the first empirical support regarding the comparative analysis on the link in corporate governance and the cost of debt in Pakistan and India.